Reception of the children’s theater - Kuyumcu, Fehime Nihal (Open Science Journal, 2017)
Reception theory or aesthetics is the name which takes part in the literary world, gives reader responsibility as well as an author about meaning or interpretation of author's works and analyze reader's function in this field. It's a matter of debate or study, who give a meaning to the work. When does the work have a meaning? Who constitutes the meaning? Reader or author? In the context of our subject, in what way does the reception process realize for theater audience and children's theater audience? Is there a difference between adult theater and children's theater? The subject of this study is to answer this question "In what way does the reception of the children's theater audience group realize among the children 4 aged and older in our country? " in the light of the cognitive development theory of Piaget and the reception aesthetics of W. Iser and we grounded the observations that were made during the children's plays and the interviews made after the play.